Identification of COVID-19 and Dengue Host Factor Interaction Networks Based on Integrative Bioinformatics Analyses - Zheng, Wenjiang; Wu, Hui; Liu, Chengxin; Yan, Qian; Wang, Ting; Wu, Peng; Liu, Xiaohong; Jiang, Yong; Zhan, Shaofeng (Frontiers in Immunology, 2021)
Background: The outbreak of Coronavirus disease 2019 (COVID-19) has become an international public health crisis, and the number of cases with dengue co-infection has raised concerns. Unfortunately, treatment options are currently limited or even unavailable. Thus, the aim of our study was to explore the underlying mechanisms and identify potential therapeutic targets for co-infection. Methods: To further understand the mechanisms underlying co-infection, we used a series of bioinformatics analyses to build host factor interaction networks, elucidate biological process and molecular function categories, pathway activity, tissue-specific enrichment, and potential therapeutic agents. Results: We explored the pathologic mechanisms of COVID-19 and dengue co-infection, including predisposing genes, significant pathways, biological functions, and possible drugs for intervention. In total, 460 shared host factors were collected; among them, CCL4 and AhR targets were important. To further analyse biological functions, we created a Protein-protein interaction (PPI) network and performed Molecular Complex Detection (MCODE) analysis. In addition, common signalling pathways were acquired, and the Toll-like receptor and NOD-like receptor signalling pathways exerted a significant effect on the interaction. Upregulated genes were identified based on the activity score of dysregulated genes, such as IL-1, Hippo, and TNF α. We also conducted tissue-specific enrichment analysis and found ICAM-1 and CCL2 to be highly expressed in the lung. Finally, candidate drugs were screened, including resveratrol, genistein, and dexamethasone. Conclusions: This study probes host factor interaction networks for COVID-19 and dengue and provides potential drugs for clinical practice. Although the findings need to be verified, they contribute to the treatment of co-infection and the management of respiratory disease.